2013
DOI: 10.1007/s11262-013-0991-2
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya emergency in China: microevolution and genetic analysis for a local outbreak

Abstract: A small-scale local chikungunya outbreak occurred in a Guangdong village of southern China in October 2010. The five chikungunya viruses (CHIKV) isolated from the epidemic and three other imported cases obtained from the same period were sequenced and analyzed for phylogenesis. The results demonstrated that all of the eight sequences were clustered in the Eastern, Central, Southern, and African group. However, the local strains and imported isolates showed different sequence variations. A226V in E1 gene and V2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…All the sequenced CHIKV strains clustered within the ECSA genotype. These sequences showed 100% similarity in the analyzed regions to sequences reported from China in 2012 . In addition, the study sequences were found to be 99% similar with samples reported from France and Hyderabad, India .…”
Section: Discussionsupporting
confidence: 67%
“…All the sequenced CHIKV strains clustered within the ECSA genotype. These sequences showed 100% similarity in the analyzed regions to sequences reported from China in 2012 . In addition, the study sequences were found to be 99% similar with samples reported from France and Hyderabad, India .…”
Section: Discussionsupporting
confidence: 67%
“…The Kenyan isolates shared similarity with the imported isolates in China which had a 90% nucleotide identity related to the ECSA within Indian Ocean lineage [ 43 ]. Detection of similar isolates over wide geographical areas shows how fast and wide impacts can be felt from the countries where the outbreaks originally started [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ECSA strains are presently circulating in many Asian countries namely India, Sri Lanka, Bhutan, China, Singapore, Cambodia and Vietnam that originated from a cluster of the epidemic strains [45][46][47][48][49]. The other branch of the epidemic strains diverged into the sequences reported in recent years from Thailand, Sri Lanka and American regions (including Brazil, Mexico and USA).…”
Section: Epidemiology and Infectionmentioning
confidence: 99%